UMP and IWATE University further boost cooperation in engineering field - Zuryaty, Zol (Pejabat Naib Canselor, 2016)
Universiti Malaysia Pahang (UMP) and Japan’s Iwate University (IU) had stepped up their strategic cooperation in strengthening the engineering field by signing a Memorandum of Understanding (MoU) that extended the partnership to another five years.